2007
DOI: 10.1111/j.1365-2486.2007.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on structure and diversity of fish communities in rivers

Abstract: It is widely accepted that climate change constrains biota. Yet, because of the lack of consistent multisite and multitaxon surveys, few studies have addressed general rules about how climate change impacts on structure and diversity of animal communities. Especially, the relative influence of nonclimatic anthropogenic disturbances on this impact is fairly unknown. Here, we present for the first time a meta-analysis assessing the effect of global warming on stream organisms. Fish communities of large rivers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
192
10
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(232 citation statements)
references
References 42 publications
19
192
10
11
Order By: Relevance
“…For the EQR only small poor quality mountain streams showed increasingly negative ratios with increasing multipliers. The FRI indicating a more downstream influenced community is in line with other studies on climate change effects on fish [19,29,30]. The actual differences in FRI of the communities range from a negligible −0.03 in poor small lowland and good small mountain streams, up to 0.37 in small good lowland streams; they are thus on average lower than the zonal changes modelled by Pletterbauer et al [19] for three future emission scenarios (A1b, A2, and B1).…”
Section: Changes In Community Metricssupporting
confidence: 75%
See 1 more Smart Citation
“…For the EQR only small poor quality mountain streams showed increasingly negative ratios with increasing multipliers. The FRI indicating a more downstream influenced community is in line with other studies on climate change effects on fish [19,29,30]. The actual differences in FRI of the communities range from a negligible −0.03 in poor small lowland and good small mountain streams, up to 0.37 in small good lowland streams; they are thus on average lower than the zonal changes modelled by Pletterbauer et al [19] for three future emission scenarios (A1b, A2, and B1).…”
Section: Changes In Community Metricssupporting
confidence: 75%
“…The actual differences in FRI of the communities range from a negligible −0.03 in poor small lowland and good small mountain streams, up to 0.37 in small good lowland streams; they are thus on average lower than the zonal changes modelled by Pletterbauer et al [19] for three future emission scenarios (A1b, A2, and B1). We did not further analyze EQR in fish assessment results due to missing key influential components for fish assessments, particularly size and age structure, which have been shown to change due to climate change [30].…”
Section: Changes In Community Metricsmentioning
confidence: 99%
“…Climate change may affect environmental conditions, and subsequently bioinvasions, by altering the pool of potential invaders and influencing the chance that non-native species will establish (Rahel and Olden 2008). Studies on the effects of climate change in lake and river systems have shown changes in freshwater species composition and diversity for fish (Buisson et al 2008;Daufresne and Boet 2007) and macroinvertebrates (Burgmer et al 2007;Chessman 2009;Daufresne et al 2004;Mouthon and Daufresne 2006). Abiotic changes in river systems typically include increases in water temperature, river dynamics and salinity (Gornitz 1991;Webb 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has a direct effect on fish activity, growth, metabolism, reproduction and development but can also influence communities and populations via biotic interactions (Petchey et al, 1999;Voigt et al, 2003;O'Connor et al, 2009;Rall et al, 2010;Yvon-Durocher et al, 2010;Ohlberger et al, 2011;Vucic-Pestic et al, 2011;Reuman et al, 2014). From this viewpoint, 1-3°C increase in temperature due to global warming have been shown to have major impacts on fish community structure and diversity (Daufresne et al, 2004(Daufresne et al, , 2009Daufresne and Boet, 2007). Temperate species generally avoid water warmer than 30°C and the temperature preference is a commonly used criterion to classify fish into cold and warm water species (Holcik et al, 1989;Wehrly et al, 2003).…”
Section: Water Temperaturementioning
confidence: 99%